O ritual dos sádicos: cinema popular, experimental e subversivo nos anos de chumbo - Silva, Andre Renato Oliveira [UNIFESP] (2019)
This dissertation aims to research the cinematographic work of the director / actor / writer José Mojica Marins, particularly in regard of the most emblematic character he created and played: the sadistic gravedigger called Coffin’ Joe. The analysis will cover, specifically, the feature film entitled "Ritual dos Sádicos" (or "The Awakening of the Beast"), produced in 1970, with distribution completely prohibited by the censorship organs of the military dictatorship prevailing in Brazil during the period. It will be highlighted the great popular reception that the character - and the films in which it appears - obtained during the years 1960-70, causing it to "spill" through other media: comic books, folklore fiction literature etc., in addition to the critical fortune that rejected the work of the filmmaker, mostly. The film will also be analyzed according to elements characteristic of the genre called film-essay, and using – as reference – studies carried out by, among others, Theodor W. Adorno and Timothy Corrigan. The main objectives are: to situate the film, in its formal elements and content, within the set of productions categorized as film-essay; to situate the film within the set of cinematographic productions made during the most repressive period of the Brazilian military dictatorship (1968-1975), productions that suffered state censorship and (or) promoted in their film discourse a critique of the current regime; to try tracing the genetic procedures of the film, particularly in regard of its essayistic aspect (with obvious political positions), since its author, until then, refused to make politicized films. This research will seek to demonstrate that the work of José Mojica Marins allegorically represents (from the concept of allegory in Walter Benjamin and other authors) - although not in a programmatic way - the institutional violence practiced by the Brazilian State during the military dictatorship, particularly in the forms of: 1. torture; 2. censorship applied to artistic-cultural manifestations.